News media representation of homosexuality: an overview / Mohd Shahnawi Muhmad Pirus, Ilias Md. Salleh and Mokhtar Muhammad - Muhmad Pirus, Mohd Shahnawi; Md. Salleh, Ilias; Muhammad, Mokhtar (2016)
The discussion on news media are always parallel with the needs of the society in disseminating information with the supports of news media tools available (de Jong, 2006), in which; (i) magazines, (ii) television, (iii) radio, (iv) newspapers, (v) movies, and the (vi) Internet—shows that the media gate keepers set the agenda of an issue for the society to be aware of from time to time, and as a tool to perpetuate one’s propaganda. Based on de Jong’s view, the researchers assume mass media practices come with several ways in exercising media analysis focusing on a particular time period to generate more in-depth insights. As stated by D’Emilio (1983), a particular time period was often chosen because it led to some bizarre events that took place giving much significance to the society’s social and cultural pattern (Gross, 2001). Based on de Jong’s view, the researcher’s prime focus of these inquiry is to get comparative apprehension on media representation of news media of homosexuality, in assuming mass media practitioners that come with general ways in exercising media analysis on a particular time period in order to generate more in-depth insights.